2018
DOI: 10.1093/annonc/mdx754
|View full text |Cite
|
Sign up to set email alerts
|

OV21/PETROC: a randomized Gynecologic Cancer Intergroup phase II study of intraperitoneal versus intravenous chemotherapy following neoadjuvant chemotherapy and optimal debulking surgery in epithelial ovarian cancer

Abstract: clinicaltrials.gov, NCT01622543.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 22 publications
(28 reference statements)
1
31
0
1
Order By: Relevance
“…The biologic, molecular, physical, and mathematical basis of this would suggest that, for an IP therapy to be effective, it should be given when the residual postsurgical disease volume is small (<1 cm) and ideally microscopic at individual sites. Several randomized trials have demonstrated significant improvements in PFS and OS with the administration of IP therapy . These IP trial designs varied, as many allowed additional dose/intensity in the IP arm, which has impeded conclusions on IP or IV administration, dose for dose.…”
Section: Treatment Of Ovarian Cancer—surgery Systemic Therapy and Rmentioning
confidence: 99%
“…The biologic, molecular, physical, and mathematical basis of this would suggest that, for an IP therapy to be effective, it should be given when the residual postsurgical disease volume is small (<1 cm) and ideally microscopic at individual sites. Several randomized trials have demonstrated significant improvements in PFS and OS with the administration of IP therapy . These IP trial designs varied, as many allowed additional dose/intensity in the IP arm, which has impeded conclusions on IP or IV administration, dose for dose.…”
Section: Treatment Of Ovarian Cancer—surgery Systemic Therapy and Rmentioning
confidence: 99%
“…However, these data have not been replicated in other studies that incorporate different patient populations, adjustments in the dosing regimens to allow for outpatient therapy, and the use of bevacizumab (GOG 252 trial). Because of the positive outcomes in the adjuvant setting, a phase 2 RCT investigated the role of intraperitoneal chemotherapy after interval debulking (OV21/PETROC trial) 48 . Although the regimen with intraperitoneal cisplatin was poorly tolerated despite the dose being decreased to 75 mg/m 2 , the intraperitoneal carboplatin regimen was well tolerated and demonstrated a trend toward fewer recurrences at 9 months.…”
Section: Principles Of Intraperitoneal Chemotherapymentioning
confidence: 99%
“…Although the regimen with intraperitoneal cisplatin was poorly tolerated despite the dose being decreased to 75 mg/m 2 , the intraperitoneal carboplatin regimen was well tolerated and demonstrated a trend toward fewer recurrences at 9 months. It is important to note, however, that the study design and endpoints of this trial were changed midway because of poor accrual, and despite the aforementioned findings, it is not considered a positive trial 48 …”
Section: Principles Of Intraperitoneal Chemotherapymentioning
confidence: 99%
“…Although 3 randomized trials using cisplatin showed a survival benefit from ip chemotherapy for optimally debulked patients with stage III ovarian cancer, 15 it has not been accepted as standard therapy, mainly because it has not been shown that ip administration of carboplatin is more efficacious than iv administration. 17 Although the OV21 study showed significant improvement in the progression-free rate at 9 months, 17 another large-scale, randomized, phase 3 study (GOG 252) failed to show a survival benefit of ip carboplatin when bevacizumab was integrated into the ip arm. 16 The OV21 trial was a 3-arm, phase 3 study designed to compare and evaluate 2 ip regimens against standard iv carboplatin/paclitaxel chemotherapy.…”
Section: Intraperitoneal Chemotherapymentioning
confidence: 99%
“…Nevertheless, in addition to the promising efficacy data, the ip carboplatin-based regimen was well tolerated with no reductions in quality of life or increases in toxicity in comparison with iv administration alone. 17 Although the OV21 study showed significant improvement in the progression-free rate at 9 months, 17 another large-scale, randomized, phase 3 study (GOG 252) failed to show a survival benefit of ip carboplatin when bevacizumab was integrated into the ip arm. 18 In the GOG 252 trial, eligible patients were randomly assigned to 1 of 3 arms: 1) the iv carboplatin arm (6 cycles of weekly iv paclitaxel at 80 mg/m 2 with iv carboplatin at AUC 6 every 3 weeks), 2) the ip carboplatin arm (weekly iv paclitaxel at 80 mg/m 2 with ip carboplatin at AUC 6), or 3) the ip cisplatin arm (iv paclitaxel at 135 mg/m 2 over 3 hours on day 1 every 3 weeks, ip cisplatin at 75 mg/m 2 on day 2, and ip paclitaxel at 60 mg/m 2 on day 8).…”
Section: Intraperitoneal Chemotherapymentioning
confidence: 99%